A Review on the Influence of Noise on the Welfare of Dogs - Raghy, R.; Jacob, Ninan; Tamizhkumaran, J. (International Journal of Bio-resource and Stress Management, 2023)
The purpose of ears is to receive and transmit sound information to the brain. All ears have a dynamic functioning range but if sounds are excessively loud, it may harm the auditory system whereas those that are too low in intensity are simply not processed. One-third of canine population suffers from noise aversion. Dogs are frequently startled by loud noises like gunshots, thunder, or fireworks. Research indicates that some dog breeds are significantly less likely to experience loud noise phobia. Older dogs are more prone to react emotionally negatively to loud noises. Extreme phobic reactions can result from a single traumatic encounter as well as recurrent exposure to frightful stimuli. While phobic responses might include panic, acute agitation, and/or destructive activity, mild fear responses can include panting, pacing and hiding attempts. Sudden, loud noises are one of the most common triggers for fearful behaviours in dogs and many companion dogs suffer from noise sensitivity. This review deals with physiology of canine ear, breed differences in hearing capacities, frequencies of sound that affect dogs and the physiological and behavioural responses of dogs to noise stress. The effect of music on canine welfare and strategies for noise abetment is also elucidated. To protect the wellbeing of dogs and to limit the emergence of anxiety-related behavioural stress issues, a better understanding of interpreting canine responses to noise is imperative.